Exploring manet security aspects: analysis of attacks and node misbehaviour issues - Islam Khan, Burhan Ul; Farhat, Anwar; Farah Diyana, Abdul Rahman; Rashidah, Funke Olanrewaju; Miss Laiha, Mat Kiah; Rahman, Md. Arafatur; Zuriati, Janin (Faculty of Computer Science & Information Technology, University of Malaya, 2022)
Mobile ad hoc networks are susceptible to various security threats due to their open media nature and mobility, making them a top priority for security measures. This paper provides an in-depth examination of MANET security issues. Some of the most critical aspects of mobile ad hoc networks, including their applications, have been discussed. This is followed by a discussion of MANETs' design vulnerability to external and internal security threats caused by inherent network characteristics such as limited battery power, mobility, dynamic topology, open media, and so on. Numerous MANET-related attacks have been classified based on their sources, behaviour, participating nodes, processing capability, and layering. The many different types of misbehaviour a node can exhibit and the various ways a node can behave were investigated. Two major types of MANETs misbehaviour have been evaluated, classified and analysed. Notably, mitigating node misbehaviour in MANET is a critical issue that must be addressed to ensure network node functionality and availability. Strategies for detecting network nodes that misroute packets are also examined. Finally, the paper emphasises the need for effective solutions to secure MANETs.